Analisis kualitatif penerapan metode muhadatsah untuk meningkatkan kemampuan berbicara bahasa arab di kelas x-f man kota pasuruan - Fauziyah, Aldina (Maliki Interdisciplinary Journal, 2025)
This research aims to describe the application of the muhadatsah method in Arabic language learning and its impact on improving the speaking skills (maharah kalam) of grade X-F students at MAN Kota Pasuruan. This study uses a qualitative descriptive approach with data collection techniques through observation, in-depth interviews, and documentation. The results indicate that the implementation of the muhadatsah method can create an active and communicative learning atmosphere, encouraging students to be more confident in speaking Arabic. Students showed improvement in aspects of pronunciation, vocabulary mastery, sentence structure formation, and speaking fluency. Although there were obstacles such as time limitations and variation in student abilities, these could be overcome through appropriate grouping and the use of engaging learning media. The muhadatsah method has proven to be an effective alternative strategy in enhancing Arabic speaking skills contextually and applicatively.